Mexico : the remaking of an economy - Lustig, Nora. (Washington, D.C. : Brookings Institution Press, 1998)
Today Mexico is viewed as a success story in the management of economic adjustment and structural reform. Inflation is under control, capital and foreign investment are returning, and out growth has increased. Mexico's recovery, however, has been neither smooth nor rapid. In mid-1982, Mexico was in deep economic crisis compounded by an unfavorable international environment. Mexico was saddled with a large foreign debt, world interest rates were high, commercial banks had stopped lending, and the price for oil was dropping. Conditions at home were no better with rampant inflation, increasing ca.
Poverty in the Primary Sector: Why Did It Rise? -- Economic Openness and Inequality -- Living Standards and the Peso Crisis -- 9. Conclusion -- Appendix: Agreement Signed by Mexico and Its Commercial Banks on Debt and Debt Service Reduction -- Notes -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y -- Z
Includes bibliographical references (pages 225-280) and index.
Print version record.
English.
JSTOR
Keywords: Mexico -- Economic policy -- 1970-1994.; Mexico -- Economic conditions -- 1982-1994.; Mexico -- Economic conditions -- 1994-; Mexique -- Politique économique -- 1970-; Mexique -- Conditions économiques -- 1982-1994.; Mexique -- Conditions économiques -- 1994-; Mexique -- Politique économique -- 1970-1994.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Economic history; Economic policy; Mexico; BUSINESS & ECONOMICS / Development / Economic Development; Since 1970